A Better 3D Conformal Approach in Glioblastoma Proximates Intensity Modulated One: A Dosimetric Study - Ullah, Sadiq; Saeed, Hashir; Shafiq, Sunnia; Ahmad, Hafiz Khush Naseeb; Manzoor, Hina (Diponegoro University Semarang Indonesia, 2025)
This study aimed to evaluate whether Three-Dimensional Conformal Radiation Therapy (3D-CRT) could achieve results comparable to Intensity Modulated Radiation Therapy (IMRT) in treating grade 4 glioblastoma. Treatment plans for 80 consecutive patients with grade 4 glioblastoma, treated between January 1, 2020, and July 31, 2024, were developed using 3D-CRT and IMRT. 3D-CRT utilized three to five fields with dynamic wedges and the field-in-field technique, while IMRT employed seven fields with homogeneous angles. Target coverage was set to ensure that 97% of the isodose covered 98% of the Planning Target Volume (PTV). Both 3D-CRT and IMRT achieved similar target coverage. However, IMRT showed superior homogeneity (0.053 vs. 0.097) and conformity (1.187 vs. 1.663) compared to 3D-CRT. IMRT also provided better sparing of normal brain tissue and surrounding organs, except for the contralateral eye, though it required longer treatment delivery time due to higher Monitor Units (MUs). IMRT additionally limited low-dose escalation. IMRT outperforms 3D-CRT in homogeneity, conformity, and sparing organs at risk, despite the longer treatment time. 3D-CRT may approximate IMRT when the target volume is not near critical structures but still results in greater low-dose exposure to normal brain tissue for the same target coverage.